Nutrition habits and physical activity of disabled adolescents in Hungary - Barabás, Ágota; Nagy, Melinda; Grestyák Molnárné, Anita Katalin; Nagy, Attila Csaba; Pazmany, Viktoria; Zahatňanská, Mária; Konečná, Mária; Sedlák, Vincent; Mydlárová Blaščáková, Marta; Poráčová, Jana; Erdei Jávorné, Renáta (Central European journal of public health, 2023)
OBJECTIVES: The overall aim of the research is to gain insight into the lifestyle and health behaviour of young people with disabilities aged 12-18 years, and to learn about the factors shaping their health. In this study, our aim was to investigate the eating habits and physical activity of adolescents with disabilities and the influencing factors. METHODS: The study's source population was young people aged 12-18 with disabilities in the Szabolcs-Szatmár-Bereg County. A total of 239 completed questionnaires were processed and analysed. Boys were overrepresented in the study. RESULTS: The results show that inadequate eating habits also exist in the population we studied, the consumption of certain foods correlates with the education level of parents. A more secure social background is a protective factor in terms of physical activity. The survey was made with the aim of intervention much needed. With precise knowledge of the health behaviour of the target group, our goal is to develop a complex intervention programme adapted to the needs of children with disabilities. CONCLUSION: The eating habits of adolescents with disabilities in the Szabolcs-Szatmár-Bereg County are unsatisfactory. Experience and results show that differentiated health promotion of young people with disabilities is necessary.
Keywords: dítě; Adolescent; stravovací zvyklosti; lidé; cvičení; Habits; Humans; zdravé chování; Male; postižení; Feeding Behavior; Hungary; Persons with Disabilities; Child; zvyky; mužské pohlaví; Maďarsko; Exercise; mladiství; Health Behavior